Pengaruh Lingkungan Kerja, Dan Pengembangan Karir, Terhadap Kinerja Karyawan Muslim Dengan Komitmen Organisasi Sebagai Variabel Intervening Pada Perusahaan Halal Food Sambel Layah Corporation Indonesia - Akhmad Darmawan; Abdan Syakuro; Fatmah Bagis (ITB AAS INDONESIA Surakarta, 2021)
This study aims to examine and analyze the effect of work environment and career development on employee performance with organizational commitment as an intervening variable on employees of Sambel Layah Corporation Indonesia. The population in this study were all permanent employees of Sambel Layah Corporation Indonesia. The sample used in this study was 120 employees using a saturated sampling technique (census). The analysis used is the Model Fit Test (F), t test, Sobel test, Regression Analysis and the Coefficient of Determination Test (R2). Based on the results of the model fit test (F) model 1 and model 2 have met the model fit test. The results of the t-test concluded; (a) the work environment has a significant effect on organizational commitment, (b) career development has a significant effect on organizational commitment, (c) the work environment has a significant effect on employee performance, (d) career development has a significant effect on employee performance, (e) organizational commitment has an effect significant to employee performance. The results of the Sobel test conclude that the work environment and career development have a significant effect on employee performance through organizational commitment. Keywords: Work Environment, Career Development, Organizational Commitment, Employee Performance